Replacing Fishmeal With Palm Kernel Meal In Formulated Feed For The Pacific White Shrimp (Litopenaeus Vannamei) - Nawwar Zawani Mamat; Norsila Daim (Airlangga University, 2021)
Utilisation of plant proteins to replace fish meal in shrimp feeds has become an important consideration because fish meal is becoming more expensive due to increasing demand worldwide. The potential use of palm kernel meal (PKM) in this study to substitute fish meal in the Pacific white shrimp (Litopenaeus vannamei) diets was evaluated by conducting a 90-day feeding trial. Shrimp juveniles with an initial average weight of 0.5 g, protein content of 10.74±0.70% were randomly distributed into five treatments in triplicates. Four isonitrogenous (approximately 35% protein) diets were formulated to contain 0% (D0), 25% (D25), 50% (D50) and 75% (D75) of PKM replacement and a commercial feed served as control treatment (Control). Results from this study revealed that shrimps fed D25 were comparable with those fed with Control as there was no significant difference (p>0.05) in weight gain and specific growth rate (SGR) between the groups. However, PKM inclusions above 50% showed detrimental effects on the growth performance. The highest total protein percent was observed in shrimp tissues fed with D25 (67.59±0.87%) and D75 showed the lowest protein among the treatments (57.4±0.63%) (p<0.05). Total lipid content was observed high in shrimps fed with Control (4.33±2.96%) and decreased with PKM replacement levels. The highest carbohydrate was found in shrimps fed with D75 (16.75±0.04%) and the lowest was found in shrimps fed with D25 (14.67±0.07%). When PKM is utilised to replace FM, a limit of 25% level should be recommended.